Quantitative and qualitative study of the structured and unstructured digital information regarding early childhood caries - Ayala Aguirre, Patricia Estefania (2022)
Early childhood caries (ECC) is an oral condition that affects 532 million children worldwide, representing a major economic and public health challenge. The present study aimed to (1) analyze the volume and profile of searches related to ECC performed by Google users from different countries, (2) evaluate the readability and quality of information related to ECC from websites in English , Spanish and Brazilian Portuguese, (3) to assess the completeness of ECC information found in Youtube videos in the same three languages, and (4) to determine the sentiment and interests of Twitter users regarding true or false/incorrect information about dental caries in the same three languages. The monthly variations in Relative Search Volume (RSV) for ECC-related queries was determined by the Google Trends API for each country. The association of RSV with years lived with disability (YLDs) for untreated dental caries in primary teeth and Internet penetration were tested by linear regression models. The most relevant topics searched by Google users were qualitatively evaluated. For the analysis of the quality of the information, the websites were retrieved by Google, Yahoo! and Bing according to the market share of each engine in the US, Mexico and Brazil. The DISCERN questionnaire, JAMA benchmarks and language-specific readability formulas were used by two independent researchers to assess the quality and readability of the websites. Completeness of information from Youtube videos was assessed by a predefined list of 17 topics related to educational information on ECC. Dichotomized categories of videos according to the median completeness score and the nature of their authorship were compared in relation to the characteristics of the videos and the parameters of interaction with the YouTube audience. To evaluate Twitter, a specific search strategy was built according to each language to collect at least 1,000 tweets for each country (USA, Mexico and Brazil). Two examiners rated tweets in their original language according to sentiment (positive, neutral, or negative), ECC-related themes, and presence of false/incorrect information based on up-to-date scientific evidence on dental caries. The results indicated that the interest of Google users for ECC information is still low, but it is increasing over time. Users interested in the disease may come across low-quality information on websites and YouTube videos. Furthermore, tweets related to dental caries containing false/incorrect information are associated with positive sentiment and are often related to missinformation about sugar consumption and the development of the disease. In conclusion, Big Data analysis is an important strategy to identify Internet users\' interests and concerns regarding ECC-related information from specific populations. In addition, understanding what parents and caregivers are exposed to when searching for information about ECC on the Internet is critical to improving disease management. Therefore, dental professionals must be attentive to the needs of their patients, producing good quality digital materials and promoting informative counseling during clinical consultations.